2021
DOI: 10.1111/apt.16488
|View full text |Cite
|
Sign up to set email alerts
|

Internal medicine hospitalisations and liver disease: a comparative disease burden analysis of a multicentre cohort

Abstract: Summary Background Liver disease is an increasing burden on population health globally. Aims To characterise burden of liver disease among general internal medicine inpatients at seven Toronto‐area hospitals and compare it to other common medical conditions. Methods Data from April 2010 to October 2017 were obtained from hospitals participating in the GEMINI collaborative. Using these cohort data from hospital information systems linked to administrative data, we defined liver disease admissions using most res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, the cohorts for the majority of these studies captured the readmission rates of all patients with cirrhosis, while this study focused on those with HE (known to increase the likelihood of rehospitalisation). Taken together with previous observations of reduced HCRU post-RFX initiation,16 17 the combined benefit of low recurrence of HE episodes, low number of complications and observed low rates of HCRU (outside of outpatient visits) support the rationale that RFX may provide a long-term economic benefit 14 31…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…However, the cohorts for the majority of these studies captured the readmission rates of all patients with cirrhosis, while this study focused on those with HE (known to increase the likelihood of rehospitalisation). Taken together with previous observations of reduced HCRU post-RFX initiation,16 17 the combined benefit of low recurrence of HE episodes, low number of complications and observed low rates of HCRU (outside of outpatient visits) support the rationale that RFX may provide a long-term economic benefit 14 31…”
Section: Discussionmentioning
confidence: 53%
“…Alternatively, the rates of complications could positively relate to the observed levels of alcohol abstinence (82%–87% between year 1 and year 5) in the ARLD cohort in which a low rate of complications might also be expected 28. Published rates of 30-day readmission due to liver-related causes vary between 18% and 37% and thus the observed rate of 37% between 1 and 5 years is at the higher end of this range 7 29–31. However, the cohorts for the majority of these studies captured the readmission rates of all patients with cirrhosis, while this study focused on those with HE (known to increase the likelihood of rehospitalisation).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, it has been found that up to 27% of CLD patients have fibrosis at diagnosis, paralleling the rising incidence of cirrhosis among Canadian adults and children over the last decade (7,8). Just as alarming, a recent study of Toronto-area hospitals shows internal medicine hospitalizations for CLD outranked other major cardio-pulmonary conditions in rates of mortality, admissions, and hospitalization costs (9). Furthermore, although the incidence of HCC in Canada is relatively low, it has been associated with the largest increase in mortality rate of all cancers.…”
Section: General Trends Related To Cldmentioning
confidence: 99%
“…This is problematic for implementing the KP method in other settings, because there are numerous troponin I assays and a separate troponin T assay, with varying reference ranges. Linear correlation between these assays does allow some standardization of troponin results, enabling the implementation of LAPS and LAPS2 [8][9][10]. However, new high-sensitivity cardiac troponin assays were introduced in 2010 and have replaced the older troponin assays in many healthcare institutions [11].…”
Section: Introductionmentioning
confidence: 99%